Hydroxytyrosol Ameliorates Endothelial Function under Inflammatory Conditions by Preventing Mitochondrial Dysfunction. (18th April 2018) - Calabriso, Nadia; Gnoni, Antonio; Stanca, Eleonora; Cavallo, Alessandro; Damiano, Fabrizio; Siculella, Luisa; Carluccio, Maria Annunziata
Abstract : Mitochondria are fundamental organelles producing energy and reactive oxygen species (ROS); their impaired functions play a key role in endothelial dysfunction. Hydroxytyrosol (HT), a well-known olive oil antioxidant, exerts health benefits against vascular diseases by improving endothelial function. However, the HT role in mitochondrial oxidative stress in endothelial dysfunction is not clear yet. To investigate the HT effects on mitochondrial ROS production in the inflamed endothelium, we used an in vitro model of endothelial dysfunction represented by cultured endothelial cells, challenged with phorbol myristate acetate (PMA), an inflammatory, prooxidant, and proangiogenic agent. We found that the pretreatment of endothelial cells with HT (1–30 μ mol/L) suppressed inflammatory angiogenesis, a crucial aspect of endothelial dysfunction. The HT inhibitory effect is related to reduced mitochondrial superoxide production and lipid peroxidation and to increased superoxide dismutase activity. HT, in a concentration-dependent manner, improved endothelial mitochondrial function by reverting the PMA-induced reduction of mitochondrial membrane potential, ATP synthesis, and ATP5 β expression. In PMA-challenged endothelial cells, HT also promoted mitochondrial biogenesis through increased mitochondrial DNA content and expression of peroxisome proliferator-activated receptor gamma coactivator 1-alpha, nuclear respiratory factor-1, and mitochondrial transcription factor A. These results highlight that HT blunts endothelial dysfunction and pathological angiogenesis by ameliorating mitochondrial function, thus suggesting HT as a potential mitochondria-targeting antioxidant in the inflamed endothelium.